Optimalization of NaOH concentration in alkaline lysis method on quality and quantity of Candida albicans DNA - Putri, Nasya Desinta; Prayekti, Endah (Journal of Indonesian Medical Laboratory and Science, 2024)
Background: The concentration of NaOH in the alkaline lysis method needs to be optimized, especially when isolating DNA for its application in PCR which has not been maximized using the Candida albicans fungus which has a complex cell wall and is difficult to break. Thus, this optimization is expected to increase the efficiency of the alkaline lysis DNA isolation method in fungal species. Objective: The purpose of this studied was to determine the effect of optimizing the concentration of NaOH in the alkaline lysis method on the quality and quantity of Candida albicans DNA. Materials and Methods: This researched is experimental by performed DNA isolation used alkaline lysis method used NaOH concentrations of 1.5 N, 1.75 N, and 2.0 N and controlled (NaOH 0.2 N). Calculation of DNA quality and quantity using a nanodrop spectrophotometer. Results: The results showed the ordered of obtained the high to low DNA quality (A260/280) was NaOH concentration 2.0 N>1.75 N>1.5 N>0.2 N (1.86±0.44-0.95±0.18) while for DNA quantity was NaOH concentration 2.0 N>1.75 N>1.5 N>0.2 N (187.7±58.3-9.6±3.5 ng/?l). Conclusion: There is an effect of optimizing NaOH concentration on the lysis of fungal cell walls in the alkaline lysis method, namely increased the purity valued and concentration of sample DNA isolation results gradually. The use of 2.0 N NaOH concentration produced the best quality and quantity of DNA, namely 1.86±0.44 for DNA quality and 187.7±58.3 for DNA quantity.